Incidence of bradycardia during noradrenaline or phenylephrine bolus treatment of postspinal hypotension in cesarean delivery: A randomized double-blinded controlled trial - de Queiroz, Daniel Vieira; Velarde, Luis Guillermo Coca; Alves, Rodrigo Leal [UNESP]; Verçosa, Nubia; Cavalcanti, Ismar Lima (Wiley, 2023)
The treatment of choice for spinal anesthesia-induced hypotension during cesarean section is phenylephrine. As this vasopressor can cause reflex bradycardia, noradrenaline is a suggested alternative. This randomized double-blinded controlled trial included 76 parturients undergoing elective cesarean delivery under spinal anesthesia. Women received noradrenaline in bolus doses of 5 mcg or phenylephrine in bolus doses of 100 mcg. These drugs were used intermittently and therapeutically to maintain systolic blood pressure ≥ 90% of its baseline value. The primary study outcome was bradycardia incidence (<60 bpm) with intermittent bolus administration of these drugs. Secondary outcomes included extreme bradycardia (<40 bpm), number of bradycardia episodes, hypertension (systolic blood pressure > 120% of baseline value), and hypotension (systolic blood pressure < 90% of baseline value and requiring vasopressor use). Neonatal outcomes per the Apgar scale and umbilical cord blood gas analysis were also compared. The incidence of bradycardia in both groups (51.4% and 70.3%, respectively; p = 0.16) were not significantly different. No neonates had umbilical vein or artery pH values below 7.20. The noradrenaline group required more boluses than phenylephrine group (8 vs. 5; p = 0.01). There was no significant intergroup difference in any of the other secondary outcomes. When administered in intermittent bolus doses for the treatment of postspinal hypotension in elective cesarean delivery, noradrenaline, and phenylephrine have a similar incidence of bradycardia. When treating hypotension related to spinal anesthesia in obstetric cases, strong vasopressors are commonly administered, thought these can also have side effects. This trial assessed bradycardia after bolus administration of noradrenaline or phenylephrine, and found no difference in risk for clinically meaningful bradycardia.